Hermite interpolation method (HiM): compact surface potential MOSFET model based on the Hermite polynomial. Issue 17 (2nd August 2016) - Colalongo, L.; Richelli, A.; Kovács‐Vajna, Zs. M.
Abstract : An extremely accurate yet simple form of the charge‐sheet model (CSM) is developed using the third‐order Hermite interpolation polynomial to model the inversion charge in the channel. This new formulation of the drain current retains the same simplicity of the most advanced surface potential compact MOSFET models based on the symmetric linearisation method (SLM). However, unlike the SLM, it is developed without requiring the crude linearisation of the inversion charge, hence the asymmetry and the non‐linearity in the channel are accurately accounted for. Nevertheless, the expression of the drain current can be worked out to be analytically equivalent to SLM. Its mathematic formulation is even easier with respect to SLM since it does not require the evaluation of the inversion charge at the surface potential midpoint, but at source and drain only, as the conventional CSM.